Study guides

Q: Can you Factor 2X2 plus 3X plus 1?

Write your answer...

Submit

Related questions

2x2 + 3x + 1 = (x + 1)(2x + 1)

(3x - 1)(2x2 - 2x - 1)

2x2-3x-5 = (2x-5)(x+1) when factored

(x + 1) / (2x3 + 3x + 5) --- Can't depict long division here, but you can work this out by seeing if (x + 1) is a factor of (2x3 + 3x + 5). If it is, then the answer will be 1/(the other factor). In this case, that is true. (2x3 + 3x + 5)/(x + 1) = 2x2 - 2x + 5, so the term term above is equal to: 1 / (2x2 - 2x + 5)

If: 2x2-3x+1 = 0 Then: x = 1 or x = 1/2

No.

(x + 1)(2x - 5)

This expression could be reordered as 1 + 3x + 2x2.

(2x + 1)(x + 1) so x = -0.5 or -1

4x4 + 1 = (2x2 - 2x + 1)(2x2 + 2x + 1)

The discriminant is 1.

(2x - 5)(x + 1) or (2x + 5)(x - 1) depending on the sign of the term 3x

(x-1)(2x+5)

x(x + 1)(x - 3)

factorises as (2x + 1)(x + 1) so x = -0.5 or -1

(2x - 1)(x - 1) so x = ½ or 1

X((x+1)^2)

9x2 + 6x + 1 = 9x2 + 3x + 3x + 1 = 3x(3x + 1) + 1(3x + 1) = (3x + 1)(3x + 1) or (3x +1)2

(-3x - 1)(3x - 7)

3x and x^2 - 3x + 1

(3x + 1)(x + 5)

(x + 5)(3x + 1)

3(x2 + 3x + 1)

3x(2y + 1)

If that's -9x^3 - 3x^2 + 3x + 1, that factors to (1 - 3x^2)(1 + 3x)